Resolution of Giant Coronary Aneurisms in a Child With Refractory Kawasaki Disease Treated With Anakinra - Gambacorta, Alessandro; Buonsenso, Danilo; De Rosa, Gabriella; Lazzareschi, Ilaria; Gatto, Antonio; Brancato, Federica; Pata, Davide; Valentini, Piero (Frontiers in Pediatrics, 2020)
Kawasaki disease (KD) is an acute, febrile illness of unknown etiology that mainly affects children under 5 years of age. intravenous immunoglobulin (IVIG), the standard treatment, has reduced coronary involvement to <5%. Patients who do not improve after an initial IVIG have a higher risk of developing coronary arteries aneurysms, and its optimal treatment remains controversial. We present a case of IVIG, steroids, and infliximab-resistant KD in a 9-month-old child, which developed giant aneurysms and was successfully treated with anakinra, a recombinant antagonist of the IL-1 receptor. In our case, the introduction of IL-1 receptor antagonist therapy seems to have blocked the disease from both a clinical and a laboratory point of view. We also noted a very rapid regression of coronary aneurysms passed from giant aneurysms to small ones, or, as in the case of the anterior descending artery, the complete disappearance of the aneurysm formation. We think that our case adds more evidences to the potential role of IL-1RA as therapy in some selected cases of refractory KD, in particular with severe involvement of coronary arteries, although new efficacy trials are needed to better understand the role of Anakinra in these patients.